听写法在提高汉语听力与写作能力中的有效性研究 - Sabinus Iden (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2026)
Dictation is one of the techniques used to assess the success of learners in Chinese language education. Through dictation, educators can simultaneously evaluate listening and writing abilities. This study aims to determine the effectiveness of dictation in improving Mandarin listening and writing skills. This research employed a classroom action research design, using observation, interviews, and self-assessment techniques for data collection, which were analyzed using descriptive qualitative methods. The study was conducted over one semester and involved 39 first-year students from Class D of the evening program at Harapan Bersama Language College. The findings indicate that students initially faced challenges such as limited vocabulary, weak listening comprehension, and poor character writing accuracy. However, after the implementation of structured dictation activities, students showed significant improvement. Quantitative results revealed that 89.7% of students achieved scores above 80, indicating a substantial enhancement in their performance. Therefore, dictation is proven to be highly effective in improving Chinese listening and writing skills.